2013
DOI: 10.1038/jcbfm.2013.225
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus after Intraventricular Hemorrhage: The Role of Thrombin

Abstract: Previous studies demonstrated that thrombin is an important factor in brain injury after intracerebral hemorrhage. This study investigated the effect of thrombin on hydrocephalus development in a rat intraventricular hemorrhage (IVH) model. There were three parts in this study. First, male Sprague-Dawley rats had an injection of 200 mL saline, autologous blood or heparinized blood, into the right lateral ventricle. Second, rats had an injection of 50 mL saline or 3U thrombin into the right lateral ventricle. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 29 publications
3
82
0
4
Order By: Relevance
“…p-mTOR mediated) that are potentially upstream of ECM protein dysregulation. 1, 5, 79, 11, 14 Multiple parallels (especially thrombin) 1, 2, 711 exist between our study, and the pathophysiology of adult intracerebral hemorrhage. 4, 5, 1214 Thus in extension: our findings may have a much broader therapeutic implication in terms of further adult stroke mechanistic study (for detailed comparisons, however—please reference 15 , these fall outside the scope of this paper).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…p-mTOR mediated) that are potentially upstream of ECM protein dysregulation. 1, 5, 79, 11, 14 Multiple parallels (especially thrombin) 1, 2, 711 exist between our study, and the pathophysiology of adult intracerebral hemorrhage. 4, 5, 1214 Thus in extension: our findings may have a much broader therapeutic implication in terms of further adult stroke mechanistic study (for detailed comparisons, however—please reference 15 , these fall outside the scope of this paper).…”
Section: Discussionsupporting
confidence: 51%
“…5 Thrombin activates a subfamily of G protein-coupled receptors, named proteinase-activated-receptors (PAR; specifically -1 and -4), 6 leading to phosphorylation and activation of mTOR 7 and increased COX-2 expression. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Our recent study showed that thrombin contributes to IVH-induced hydrocephalus. 4 There have been few studies evaluating the relationship between iron released from blood into cerebrospinal fluid (CSF) and hydrocephalus; however, there is some clinical evidence of a link between iron and posthemorrhagic hydrocephalus. Nonprotein-bound iron was found in CSF from preterm infants with posthemorrhagic ventricular dilatation compared with infants without IVH.…”
Section: Introductionmentioning
confidence: 99%
“…Increased brain HO-1 levels may accelerate heme degradation and result in brain damage after ICH and SAH 23, 38, 39 . However, some literature report a protective function 40 and, in the current study, CD47 KO blood increased HO-1 levels and was associated with reduced ICH-induced brain injury.…”
Section: Discussionmentioning
confidence: 99%